Al 6061-T6 microstructure and mechanical properties modification under ion beam irradiation at room temperature: Application for Nuclear Research Reactor - Izerrouken, Mahmoud. Sari,Ali . Menchi,Omar. Haid , Fadila. Ishaq,Ahmed . ,Hocine, Slamene (University of Eloued جامعة الوادي, 2023)
In this study, the aerodynamic performance of a small-scale drone propeller (Tmotor28 propeller) in axial flight has been analyzed using the Blade Element Momentum Theory (BEMT). Which is a powerful tool to model the aerodynamic interaction between the rotor/propeller and the fluid flow. The aim of this paper is to propose a BEMT model for the Unmanned Aerial Vehicle (UAV). An open-source tool known as pyBEMT (Python programming language) has been used to calculate the aerodynamic performance of the propeller. The XFoil, which is based on the panel-vortex methods, has been used to find the lift and drag coefficients (CD and CL) of the propeller airfoils. The numerical results have been validated with experimental results. Good agreements have been found. This study introduces a straightforward and powerful calculation method for predicting and optimizing the aerodynamic performance of drones.
Article
Keywords: Aerodynamic analysis; Blade Element Momentum; BEMT; Drone propeller; UAV